The Moderating Role of Tax Planning in the Relationship Between Current Tax Expenses, Deferred Tax Assets, and Earnings Management - Adibah Yahya; Nabila Stefany Faleri; Rina Nurjanah; Aoliyah Firasati (Owner : Riset dan Jurnal Akuntansi, 2025)
The objective of this study is to examine the relationship between current tax expense, deferred tax assets, tax planning, and earnings management practices in firms. To this end, financial data from industry sectors of food and beverages is employed in panel regression analysis to determine whether current tax expense and deferred tax assets exert a significant influence on earnings management and whether tax planning acts as a moderator in the relationship. The research method uses quantitative descriptive analysis, with sample selection using purposive sampling. The data in this study were from 20 companies in 4 years. The results showed that current tax expense has a negative effect on earnings management, while deferred tax assets have a positive effect on earnings management. Tax planning does not affect earnings management, and cannot be a moderating variable for the effect of current tax expense and deferred tax assets on earnings management. The theoretical and practical implications of the findings of this study are expected to make a significant contribution to the accounting and financial management literature